The Neuroprotective Effects of Coreopsis tinctoria and Its Mechanism: Interpretation of Network Pharmacological and Experimental Data - Ma, Pei; Zhang, Rong; Xu, Lijia; Liu, Haibo; Xiao, Peigen (Frontiers in Pharmacology, 2022)
Background: Coreopsis tinctoria Nutt. (CT), an annual herb in the genus Coreopsis, is an important traditional medicine to be used for anti-diabetes and antioxidant. Objective: The antioxidant compounds from CT may affect mitochondrial function and apoptosis, which in turn may affect related diseases. The aim of this study was to explore the potential molecular mechanism and new therapeutic opportunities of CT based on the network pharmacology. Methods: A network pharmacology-based method, which combined data collection, drug-likeness filtering, target prediction, disease prediction and network analysis, was used to decipher the potential targets and new therapeutic opportunities of CT. The potential molecular mechanism and pathway were explored through GO and KEGG analysis. Then MPTP induced SH-SY5Y cell model was applied to evaluate the neuroprotective effects and key targets. Results: There were 1011 targets predicted for 110 compounds. Most targets were regulated by flavones, phenylpropanoids and phenols, and had synergistic effects on memory impairment, pancreatic neoplasm, fatty liver disease and so on. The compounds-targets-diseases network identified TNF, PTGS2, VEGFA, BCL2, HIF1A, MMP9, PIK3CG, ALDH2, AKT1, and EGFR as key targets. The GO and KEGG analysis revealed that the cell death pathway, mitochondrial energy metabolism and PI3K-AKT signal pathway was the main pathways. CT showed neuroprotective effects via regulating gene and protein expression levels of key targets in in vitro model. Conclusion: CT had potential neuroprotective effects by targeting multiple targets related with apoptosis, which were affected by BCL-2 and AKT signaling pathway. This study provided a theoretical basis for the research of neuroprotective effects of CT.